English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

9 answers

-(x + 2) - 2x = -2(x + 1)

Distribute into the parenthesis.

-x - 2 - 2x = -2x - 2

Combine like terms.

-3x - 2 = -2x - 2

Add 3x to both sides.

-2 = x - 2

Add 2 to both sides.

0 = x

2007-08-27 14:16:54 · answer #1 · answered by its_victoria08 6 · 0 0

x=0

1) -(x+2)-2x= -2(x+1)
2) -x-2-2x= -2x-2 distribute the - on the left and the -2 on the right
3) -x=0 the -2x and the -2 on both sides cancel
4) 0=x x is added to both sides
5) x=0 switch it to get x on the left

2007-08-27 21:25:44 · answer #2 · answered by chris p 2 · 0 0

-- (x +2) -- 2x = -- 2(x +1)
=> x + 2 + 2x = 2(x +1)
=> x + 2 + 2x = 2x + 2
=> x + 2x -- 2x = 2 -- 2
=> x = 0

2007-08-27 21:19:13 · answer #3 · answered by sv 7 · 0 0

steps

1 - multiply out the brackets

2 - take x terms on one side of the equation and the other terms on the other side of the equation

like thus

x + 2 - 2x = -2x -2

=> 2-x = -2x -2
=> 2x - x = -2 -2
=> x = -4

2007-08-27 21:18:36 · answer #4 · answered by Aslan 6 · 0 1

-(x+2) - 2x = -2(x+1)

first perform all of the multiplication steps:
-(x + 2) - 2x = -2x - 1

because of the negative sign outside of the remaining parenthesis, change the signs:
-x - 2 - 2x = -2x - 1

get all the variables on one side and the integers on the other and solve:
-x = 1
x = -1

2007-08-27 21:38:39 · answer #5 · answered by peachi517 2 · 0 0

-(x+2)-2x=-2(x+1)
First, use distributive property on each side.
-x-2-2x = -2x-2
Then, sum like terms
-3x-2=-2x-2
Then add 3x to both sides and 2 to both sides to cancel out
-3x+3x-2+2 = -2x+3x-2+2
0 = x

Or, you can begin the problem by multiplying both sides of the equation by -1, to eliminate the negatives:
(x+2)+2x = 2(x+1)
Combine like terms
3x +2 = 2x +2
Subtract to put variables on one side and constants on other
x = 0

2007-08-27 21:22:19 · answer #6 · answered by Jennifer L 1 · 0 0

-(x+2)-2x=-2(x+1)
-x-2-2x = -2x-2
-x-2x+2x = -2+2
-x =0
x=0

2007-08-27 21:19:05 · answer #7 · answered by ironduke8159 7 · 0 0

Look at the LHS:
-(x+2) - 2x = -x -2 -2x = -3x - 2
Look at the RHS:
-2(x+1) = -2x - 2
LHS = RHS
-3x - 2 = -2x - 2
-x = 0
x = 0

2007-08-27 21:19:31 · answer #8 · answered by kellenraid 6 · 0 0

-(x+2)-2x=-2(x+1)
-x-2-2x=-2x-2
-3x-2=-2x-2
0=x

2007-08-27 21:22:02 · answer #9 · answered by IcyCool 4 · 0 0

fedest.com, questions and answers